Peruvian university teachers' attitudes towards work in post-pandemic times - Bázan Velásquez, Silvia Milagritos (2023)
University education has changed substantially as a function of the conditions required by the health emergency. The purpose of the study was to identify the attitudes of Peruvian university teaching staff towards work activity, in post-pandemic times, in a public university in Tacna, Peru. It was carried out in the second semester of the 2021 academic year. The research was framed in the quantitative approach, descriptive exploratory research, non-experimental cross-sectional design. There was a sample of 32 university teaching mothers and 42 university teaching fathers. The questionnaire was assigned and implemented online. Content validity was applied and obtained a high reliability. The results showed that university parent teachers presented a favorable attitude level in the cognitive, affective and behavioral dimensions, while university mother teachers presented an unfavorable attitude level in the cognitive, affective and behavioral dimensions, due to the lack of support, product of the social isolation that has led to configure a post-pandemic feminized context that responds to the changes caused by the health emergency and the transition from face-to-face education to remote education in emergency. It is necessary the reconstruction of work practices, in relation to teaching, research, extension, management and domestic work, under a new normality of reality, in order to provide welfare and health to university teaching staff.